Κ0 for soil sites: Observations from KiK-net sites and their use in constraining small-strain damping profiles for site response analysis. Issue 1 (February 2020) - Xu, Boqin; Rathje, Ellen M; Hashash, Youssef; Stewart, Jonathan; Campbell, Kenneth; Silva, Walter J
Small-strain damping profiles developed from geotechnical laboratory testing have been observed to be smaller than the damping inferred from the observed site amplification from downhole array recordings. This study investigates the high-frequency spectral decay parameter ( κ 0 ) of earthquake motions from soil sites and evaluates the use of κ 0 to constrain the small-strain damping profile for one-dimensional site response analysis. Using data from 51 sites from the Kiban-Kyoshin strong motion network (KiK-net) array in Japan and six sites from California, a relationship was developed between κ 0 at the surface and both the 30-m time-averaged shear wave velocity ( V s 30 ) and the depth to the 2.5 km/s shear wave velocity horizon ( Z 2.5 ). This relationship demonstrates that κ 0 increases with decreasing V s 30 and increasing Z 2.5 . An approach is developed that uses this relationship to establish a target κ 0 from which to constrain the small-strain damping profile used in one-dimensional site response analysis. This approach to develop κ 0 -consistent damping profiles for site response analysis is demonstrated through a recent site amplification study of Central and Eastern North America for the NGA-East project.